Practicing 21st Century Skills for SMPN 1 Aikmel Students through A Scientific Approach with a Lesson Study Model - Marhamah, Marhamah; Maimunah, Maimunah; Amin, Khalikul; Misnawati, Misnawati (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2023)
The purpose of this study was to train 21st century skills for SMPN 1 Aikmel students through a scientific approach with a Lesson Study model. The research method used is descriptive qualitative, which examines the process of learning science divided into several cycles to reveal the facts of learning. The subjects in this study were class VII students of SMPN 1 Aikmel. Lesson Study was carried out in two cycles, each cycle consisting of the stages of Plan (composing Lesson design), Do (open class), See (learning reflection), Redesign Lesson design, Do (open class), and See (learning reflection). Based on the results of observations that have been made, it was obtained data on student collaboration skills of 75.1%, critical thinking skills of 72.4%, and literacy skills of 72.5%. From the data it can be concluded that overall collaboration skills, critical thinking skills and literacy skills are in the high category. The results of the study showed that there were changes in students' collaboration skills, literacy skills and critical thinking skills because they were trained through a scientific approach in each cycle of the science learning process that was carried out